Cognitive bias modification in the context of depression: interpretation bias and mental imagery - Lang, T (2009)
The aim of this thesis was to develop a positive Cognitive Bias Modification (CBM) technique using imagery in the context of depressed mood. CBM targets biases associated with emotional disorders. CBM modifying interpretation bias (CBM-I) has been investigated for anxiety, but not depression. Whilst many cognitive processes contribute to depression, the current focus was on mental imagery and interpretation bias. In a series of six studies a positive, imagery-oriented CBM-I was developed, culminating in a final test in a clinically depressed population. Prior research had demonstrated that for positive CBM-I, a verbal rather than imagery condition was not only less effective at promoting positive mood, but led to mood deterioration. Experiment 1 investigated what aspect of verbal processing might be responsible for the paradoxical increase in negative emotion. Results suggested that unfavourable comparisons between the self and the positive CBM-I material was driving the increased negativity. Experiment 2 investigated whether making such comparisons in an imagery mode would yield similar effects and whether field perspective imagery instructions would enhance positive CBM-I. Results indicated that optimal instructions for CBM-I should include field perspective imagery whilst discouraging comparative processing. Studies 3a and 3b investigated the relationship between interpretation bias, mental imagery and depressive symptoms in a large sample. Interpretation bias discriminated between low and high dysphoric participants, who had a greater frequency of negative intrusive images. To target negative intrusive images, a new CBM-I technique was developed in Study 4 and Experiment 5 - "CBM of appraisals". Compared to negative CBM of appraisals training, positive training led to fewer intrusive memories and less intrusive symptomatology concerning a depressive film after one week. Finally in Experiment 6, a multi-component CBM-I package (including auditory CBM-I from Experiments 1 and 2; CBM of appraisals from Study 4 and Experiment 5; plus a picture-word technique) was tested in 24 participants with clinical depression. Positive compared to neutral multi-component CBM-I led to improvements in interpretation bias, appraisal bias, depressive and intrusive symptoms. This suggests the potential clinical benefit of a multi-component positive imagery-oriented CBM-I package.